Lactic acidosis complicating treatment of ketosis of labour. Issue 5997 (13th December 1975) - Ames, A C; Cobbold, S; Maddock, J
Abstract : Hypertonic glucose, fructose, and sorbitol solutions were given intravenously to women in the first stage of labour who had ketonuria and ketonaemia as evidenced by a raised blood acetoacetate and 3-hydrosybutyrate. There was no difference in the antiketogenic action of these, which was rapid and effective, but when compared with a control group who were given normal saline they had a high incidence of hyperlactataemia, and nine out of 28 patients developed lactic acidosis after the infusions. The "lactatogenic" effect was shared by all three substrates, and when they are used in the treatment of ketosis of labour, and the mother develops lactic acidosis, they might exacerbate pre-existing lactic acidosis and precipitate fetal distress.